Effect on Vitamin D supplements and Fatty Acids in management of cardiovascular diseases - Layla Abd-Al-Sattar Sadiq Laylani; Adwaa Fezaa Jassim; Ansam Hussein Ali; Mohamed Ahmed Mustafa (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: n-3 polyunsaturated fatty acids (PUFA) and vitamin D exclusively and have been the focus of numerous research regarding their possible significance in lowering cardiovascular risk. Numerous physiological processes, including signal transduction, ion channel kinetics, and protein and membrane trafficking are modulated in part by lipid microdomains. The inclusion of n-3 PUFA modifies the physical characteristics of cellular and organelle membrane structures and affects the positioning, functioning, and signaling of membrane-associated proteins. Aims and Objectives: To analyze the effect of vitamin D supplements and fatty acids on the management of cardiovascular diseases. Methods: This is a prospective study which was conducted on 80 patients for whom cardiovascular abnormalities were considered and their parameters were determined before administration of n3 fatty acids and Vitamin D3. After 6 months course of drugs containing n3 fatty acids and Vitamin D3, the cardiovascular abnormalities including mortality were assessed for end outcome. The statistical analysis was conducted to determine the significance of the improvement. Results: The study found that end assessment showed that ischemic stroke (p=0.032) and cardiovascular mortality (p=0.023) were significantly found to be less in the n-3 FAs group and vitamin - D group compared to the control group. Conclusion: The study concluded that administration of n-3 FAs group and vitamin - D at a mentioned dosage for 6 months may lead to a statistically significant reduction in cardiovascular mortality and ischemic stroke as compared to healthy controls.